Alcohol Availability, Use, and Harms Among Adolescents in Three Mexican Cities. (June 2020) - Ringwalt, Christopher L.; Paschall, Mallie J.; Grube, Joel W.; Miller, Ted R.; Warren, Kenneth R.; Gidi, Virginia; Fisher, Deborah A.; Goldberg, Allison
Alcohol remains readily available to youth in most countries. We examined the associations between both the on- and off-premises commercial availability of alcohol to youth and their alcohol use, heavy episodic drinking, and alcohol-related harms. We conducted the study using data from a survey of a sample of 594 students in central Mexico between 12 and 17 years of age in 2016. Both the perceived availability of alcohol and the purchasing of alcohol at an off-premises establishment were positively related to past-30-day alcohol use and heavy episodic drinking, as well as to alcohol-related harms in the past year. Consumption at on-premises establishments was also positively associated with alcohol-related harms. Preventive efforts to reduce the availability of alcohol at off- and on-premises establishments, by such strategies as mystery shopper and responsible beverage service programs, are imperative.